MOTIVASI KERJA GURU PAUD (Studi Kasus Guru PAUD di Kecamatan Sayung Kabupaten Demak) - Ulfa Nur Aini, 14.05.51.0030; Basukianto, Basukianto (Students' Journal of Economic and Management, 2018)
Early childhood teachers are one of the most important parts for early childhood education. But actually the salary earned by early children teachers during work can be categorized as inadequate. That inadequate salaries can trigger low motivation owned by an early childhood teachers to produce good quality work. But based on the facts that exist even though teachers have inadequate salaries, they still have a high motivation in working and teaching so that the impact on the quality of good work. This study aims to determine the motives affecting early childhood teachers in Sayung, and the most dominant motive of influence on early childhood teachers in Sayung. This research is expected to contribute in the addition of reference scientific studies on the motivation of early childhood teachers. The population in this study were all early childhood teachers in Sayung, which amounted to 163 people. The sample in this research is stratified sampling, where the respondents are used as the sample is differentiated based on education level. Data collection in this study using questionnaire. The results showed that the influence of high work motivation of an early childhood teacher is physiological motives, esteem motives, and self-actualization motives. Three of them also have a good effect on the quality of work produced by early childhood teachers. However, self-actualization motif became the most dominant motive that influenced early childhood teachers in Sayung. Keywords: Motive, Motivation, Physiological, Esteem, Self Actualization, and Early Childhood Teacher